Stress, kisspeptin, and functional hypothalamic amenorrhea. (December 2022) - Meczekalski, Blazej; Niwczyk, Olga; Bala, Gregory; Szeliga, Anna
Abstract: Functional hypothalamic amenorrhea (FHA) is the most common cause of secondary amenorrhea in women of reproductive age. FHA is predominantly caused by stress, decreased caloric intake, excessive exercise, or a combination thereof. These physical, psychological, and metabolic stressors cause aberration in the pulsatile release of gonadotropin-releasing hormone (GnRH) and subsequently impair function of the hypothalamic–pituitary–ovarian (HPO) axis. Various neurotransmitters acting in the central nervous system are involved in control of the HPO axis and of these, kisspeptin is one of the most important. Corticotropin-releasing hormone (CRH), also inhibits the pulsatile secretion of GnRH and also acts as an intermediary between stress factors and the reproductive system. One of the main ongoing concerns in patients with FHA is chronic hypoestrogenism, a condition, which is associated with sexual dysfunction and infertility. It may also lead to osteoporosis, and predispose to neurodegenerative and cardiovascular diseases. Treatment of FHA requires the elimination of causative factors, however, making the necessary lifestyle changes is not always easy to initiate and maintain. Broadening our knowledge of the complex neural mechanisms regulating reproductive function in which kisspeptin plays a key role can help in the development of new treatment options such as the potential of kisspeptin receptor agonists for patients with FHA.